Characteristics of headaches attributed to SARS-CoV-2 vaccination and factors associated with its frequency and prolongation: a cross-sectional cohort study - Jameie, Melika; Togha, Mansoureh; Azizmohammad Looha, Mehdi; Jafari, Elham; Yazdan Panah, Mohammad; Hemmati, Nima; Nasergivehchi, Somayeh (Frontiers in Neurology, 2023)
Background: Headache is the most frequent neurological adverse event following SARS-CoV-2 vaccines. We investigated the frequency, characteristics, and factors associated with post-vaccination headaches, including their occurrence and prolongation (≥ 48 hours).: In this observational cross-sectional cohort study, retrospective data collected between April 2021-March 2022 were analyzed. Univariate and multivariate logistic regressions were used to evaluate the effect of clinicodemographic factors on the odds of post-vaccination headache occurrence and prolongation.Results: Of 2500 people who were randomly sent the questionnaire, 1822 (mean age: 34.49 ± 11.09, female: 71.5%) were included. Headache prevalence following the first (V1), second (V2), and third (V3) dose was 36.5%, 23.3%, and 21.7%, respectively (P< 0.001). Post-vaccination headaches were mainly tension-type (46.5%), followed by migraine-like (36.1%). Headaches were mainly bilateral (69.7%), pressing (54.3%), moderate (51.0%), and analgesic-responsive (63.0%). They mainly initiated 10 h [4.0, 24.0] after vaccination and lasted 24 h [4.0, 48.0]. After adjusting for age and sex, primary headaches (V1: